Early massive gastrointestinal bleeding as a complication of left ventricular assist device implantation - Redžek, Aleksandar; Preveden, Andrej; Golubović, Miodrag; Gocić Perić, Nataša; Popov, Tanja; Petrović, Milovan; Nikolić, Ivan; Jakovljević, Djordje G.; Velički, Lazar (Vojnosanitetski pregled, 2021)
Introduction. Implantation of left ventricular assist device (LVAD) improves survival and quality of life in patients with end-stage heart failure. We reported a case of a severe gastrointestinal bleeding as a life threatening complication in early recovering postoperative period of continuous blood flow LVAD implantation. Case report. The patient had a history of heart failure due to ischemic cardiomyopathy with low systolic function, as an indication for LVAD implantation. The operation and the postoperative course were uneventful. On the 17th postoperative day, the patient developed severe anemia, which was followed by melena with blood clots. Endoscopic examinations revealed diffuse colonic bleeding. Oral anticoagulation therapy was discontinued, and fresh frozen plasma, K vitamin substitution, and human prothrombin complex were administered. The LVAD speed was reduced and subcutaneous administration of somatostatin analog octreotide was initiated. These measures successfully stopped the bleeding and the patient was stabilized. Due to a multidisciplinary team approach, the bleeding was successfully managed and the patient recovered. Conclusion. Acute gastrointestinal bleeding represents a serious, life-threatening condition that can develop after LVAD implantation, but with timely and appropriate measurements, it can be successfully treated.